GIS-material for the archaeological project: A Bronze and Iron Age settlement in Veta - Mantorp - Swedish National Heritage Board, UV Öst (Uppsala University, 2024)
The information in the abstract is translated from the archaeological report:
Due to a new local plan within the property Veta 5:5 and others in Mantorp, Mjölby municipality, the Swedish National Heritage Board's Contract Archaeology Service, UV Öst, performed an assessment (phase 2) and a field evaluation in 2004. A total of 75 features were found, such as hearths, post holes, pits and ard marks. The remains have got a temporary registration number; UV 4, Vera parish. Iron Age pottery and burnt clay was also found as well as remains of several settlement and agricultural layers overlying each other and disturbed by ploughing. Features were also found underneath these layers. The dating of six features show that the remains cover, at least, a time span from the early Bronze Age to the Migration Period.

Purpose:
The information in the purpose is translated from the archaeological report:
The purpose of the assessment (stage 2) was to determine whether any archaeological remains were going to be affected by the development. The purpose of the field evaluation was to delimit the settlement and cultivation areas, to determine their scientific potential and to find out if there are any other prehistoric or historical remains within the area.

The data is available in two formats: a ZIP file containing GIS shapefiles connected to an Access datafile containing information pertaining to excavation area, finds, object types along with other metadata regarding the archaeological investigation. The second ZIP file consists of corresponding .gml and .xlsx files.

Informationen i sammanfattning är hämtad ur rapporten för undersökningen:
Inför ny detaljplan för Veta 5:5 med flera i Mantorp, Mjölby kommun utförde Riksantikvarieämbetet UV Öst under 2004 en arkeologisk utredning etapp 2 och en förundersökning inom exploateringsområdet. Sammanlagt under utredningstillfället och förundersökningen påträffades omkring 75 anläggningar i form av härdar, stolphål, gropar och årderspår. Fornlämningsområdet är i avvaktan på tilldelning av RAÄ-nr noterat i fornlämningsregistret som UV 4 Veta socken. Fynd gjordes av järnålderskeramik samt av bränd lera. Delar av nedodlade boplats- och odlingslager kunde konstateras i flera skikt. Under dessa lager påträffades också anläggningar. Dateringar av sex anläggningar visar att lämningarna åtminstone täcker ett tidsspann från äldre bronsålder till folkvandringstid.

Syfte:
Informationen i syfte är hämtad ur rapporten för undersökningen:
Syftet med den arkeologiska utredningen, etapp 2, var att avgöra om lagskyddade fasta fornlämningar kan komma att beröras av exploateringen. Syftet med den arkeologiska förundersökningen var att begränsa boplats- och odlingsytorna och att fastställa deras arkeologiska potential och om det fanns ytterligare förhistoriska eller medeltida lämningar av annan karaktär inom området.

Data finns tillgängligt i två olika format: en ZIP-fil innehåller GIS-filer (shp) samt en Access datafil vilka innehåller information om schakt, fyndföremål, lämningstyper samt annan metadata om den arkeologiska undersökningen. Den andra ZIP-filen består av gml- och xlsx-filer med motsvarande data
GIS-material för arkeologiskt projekt: En brons- och järnåldersboplats i Veta - Mantorp
Keywords: Iron Age; järnålder; Bronze Age; bronsålder; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi; Fieldwork archive; Fieldwork archive